Cavitation-Enhanced Drug Delivery and Immunotherapy - Helfield, Brandon; Sirsi, Shashank; Kwan, James; Gray, Michael (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Cavitation-Enhanced Drug Delivery and Immunotherapy is a rapidly evolving area that has been buoyed in recent years by the development of methods harnessing the activity of ultrasound-stimulated bubbles, known as cavitation. When properly controlled, cavitation can help overcome physical barriers to drug delivery whilst providing readily measurable information for timely quantitative feedback and treatment guidance. Microbubble-assisted therapies have demonstrated impressive advancements in clinical trials and pre-clinical areas, including applications in neurology, oncology, cardiology and beyond.